Penerapan sistem akuntansi berbasis akrual: kajian dari aspek keperilakuan - Teguh Erawati; Danang Kurniawan (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This study aims to determine the effects of organizational commitment, human resources, and the utilization of information technology on the implementation of accrual-based governmental accounting standards. Using the purposive sampling method, this study has 45 department heads, sub-department heads, and staff of the finance department in each local government agency (SKPD – Satuan Kerja Perangkat Daerah) of Magelang Regency as the respondents. The study modifies the questionnaire from previous literature to generate the primary data. The results show that organizational commitment affects the implementation of accrual-based governmental accounting standards. However, two other independent variables (human resources and the use of information technology) have no effect on the application of accrual-based governmental accounting standards.